Vertical vibration of the vehicle when crossing over transverse speed bumps - Klimenda, Frantisek; Soukup, Josef; Skočilasová, Blanka; Skočilas, Jan (Manufacturing Technology Journal, 2020)
The experimental investigation of the vertical vibration of the vehicle is presented. The vibration of the two axles vehicle is excited by crossing of the vehicle over the transverse speed bumps on the road. The methodology is oriented upon the quarter, half and full model solution. The full geometry model is the most suitable model for the vertical vibration of the vehicle. The full geometry model is capable to describe geometric and construction asymmetry of the vehicle. The methodology of an analytical solution of the symmetry and asymmetry distribution of the vehicle and load is presented. Also, symmetric and asymmetric excitation is involved to the solution. The Heaviside?s function is applied for the excitation of vibrations. The presented methodology was applied to the experimental work with trolleybus Tr 21. The normalized speed bumps were used for the experimental setup. The vertical displacements, velocities and accelerations of axles, body of the vehicle. The acceleration of the vehicle chassis under driver seat was also recorded. This accelerations have significant effect on the comfort of driver and consequently on his/her fatigue and health condition.
Keywords: Vibration; Trolley Bus; Retarder; Axle; Self-Supporting Body